Dual Purpose Corn Hybrids (Grain-Silage) Performance Assessment in Northeastern Kansas. I. Grain Yield - Felicitas Vignati; Lucas Lingua; W. E. Brown; Ignacio Antonio Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
Dual-purpose corn (Zea mays L.) hybrids are capturing the attention of farmers due to their versatility, as their final use can be decided for either grain or silage. This study compared eight dual-purpose corn commercial hybrids. During the 2023 growing season, a dryland field experiment was conducted in Manhattan, KS (US). We analyzed grain yield differences and the numerical and physiological yield components between hybrids. Furthermore, we assessed the hybrids’ grain dry-down rates, which are crucial to optimize harvest time and minimize post-harvest losses. Grain yield ranged from 141.5 to 182 bu/a, and the grain number explained more of this variation than grain weight. The harvest index values varied narrowly between 0.46 and 0.51. Hybrids with higher yields also exhibited greater biomass. Additionally, the study uncovered three distinct patterns in the rate of kernel moisture loss, clarifying the dry-down process.
Keywords: silage yield; corn; grain yield components; dry down